FRACTIONAL COMPOSITION OF HUMIC ACIDS IN SOILS AND δ13C DISTRIBUTION IN FRACTIONS - Dobrovol'skii V.V.; Aleshchukin L.V.; Kodina L.A. (My University, 2004)
The fractional composition of humic acids (HA) as stable Corg forms in the biosphere has been studied for soils of two types (chernozem and dernovo-podzolic) with different mechanisms of humus formation. Radiocarbon ages of HA in the modern and Late Holocene chernozems indicate the stability of the HA fraction. General and specific features of δ13C distribution in soils are discussed on the basis of carbon isotopic composition of HA fractions.